Dynamic Mechanics‐Modulated Hydrogels to Regulate the Differentiation of Stem‐Cell Spheroids in Soft Microniches and Modeling of the Nonlinear Behavior. Issue 30 (11th June 2019) - Zhang, Jianguang; Yang, Hua; Abali, Bilen Emek; Li, Mingjun; Xia, Yi; Haag, Rainer
Abstract: Although mechanisms of how physical forces convert into biochemical signals are increasingly understood, it is still unknown how soft cues guide cell behavior. Herein, it is shown that the commitment and differentiation of encapsulating human mesenchymal stem cell (hMSC) spheroids in thermosensitive 3D hydrogels are simply altered by interpenetrating poly( N ‐isopropylacrylamide‐ co ‐2‐hydroxyethyl methacrylate) (NIPAM‐HEMA) nanogel to a gelatin methacryloyl (GelMA) network. This cell‐laden hydrogel provides dynamic mechanics with covalent crosslinking coordinated reversible physical networks, which can regulate hMSCs in situ by reversibly stiffening soft niches via multicyclic temperature changes from 25 to 37 °C. The spreading of hMSC spheroids in the hydrogel is strongly dependent on myosin‐dependent traction stress with dynamic mechanical stimuli through focal adhesion kinase (FAK) signaling. Notably, the dynamic microenvironment gradually influences the expression and distribution from the basal to apical side of nuclear lamin A/C and increases the Yes‐associated protein (YAP) nuclear localization with cycles, which ultimately favors hMSCs undergoing osteogenesis (but not adipogenesis) in the soft microniche. Moreover, it is demonstrated that the viscoelastic behavior of the soft microniche can be guided by temperature through a nonlinear model. These findings highlight the central roles of the dynamic relationship between the biomechanical signals and mechanosensitive transcriptional regulators in cellular mechanosensing. Abstract : Nanogel‐actuated‐integrated responsive hydrogels are able to modulate the stiffness in a soft microniche with covalent crosslinking coordinated reversible physical networks, which can regulate the differentiation of stem‐cell spheroids. The central roles of the dynamic relationship between the biomechanical signals and mechanosensitive transcriptional regulators in the cellular mechanosensing are presented.